PENERAPAN PEMBELAJARAN BERDASAR MASALAH UNTUK MENGATASI KESULITAN SISWA DALAM MENGERJAKAN SOAL BERCIRIKAN KETERAMPILAN PROSES - Suyono Suyono (Jurnal Cakrawala Pendidikan, 2007)
This article concerns a research intended to overcome students' inability in doing a process-skills test by implementing problem-based instruction (PBI). The descriptieve indicators of the research were successful learning of syntax via PBI (as an element of the process dimension) and the student's score in implementing cognitive process skills (as an element of the product dimension). The research was therefore a classrtoom action reseacrch (CAR) and it as conducted in three cycles. Each cycle consisted of the following steps.: Planing the action, implementing the action, observation, and reflection. The results of the research indicattd tha (1) the implementation of the problem-based instruction could improve students' learning activities throughout the three cycles and (2) the implementation of the problem-based instruction could overcome students inability in doing the process-skills test.